Prediction of marathon performance time on the basis of training indices - Tanda, G. (Journal of Human Sport & Exercise, 2011)
The purpose of this study was to examine the relationship between marathon performance time (MPT) and some training factors recorded for a given number of weeks prior to a race. Twenty-two runners, age 28-54 years, participated as subjects in this investigation. They kept daily exercise records during their marathon training for an overall number of 46 races, whose marathon time ranged from 167 to 216 min. Among the several parameters investigated, MPT was found to be affected mainly by the mean distance run per week K, during the training period under observation, and by the mean training pace P. These two training parameters have been combined by a mathematical approach to give a correlation for the prediction of the mean marathon pace Pm (easily related to MPT), based on an 8-week training period, as follows: Pm (sec/km) = 17.1 + 140.0 exp[-0.0053 K(km/week)] + 0.55 P (sec/km). The above correlation is able to estimate the MPT with a SEE of about 4 min.